Approche de l'état physiologique de l'huître creuse Crassostrea gigas au cours d'un cycle saisonnier à Marennes-Oléron - Moal, Jeanne; Samain, Jean-francois; Bodoy, Alain; Le Coz, Jean-rene (Société Française de Malacololgie, 1987)
The energy charge was measured for two Crassostrea gigas populations, during an annual survey at Marennes Oleron, to appreciate the condition of health of these oysters. It is assumed that the actual decrease in production of this area is related to a biomass overload which affects the oysters by lowering their scope for growth. Energy charge, an index developped by ATKINSON (1968), defines the energy equilibrium of organisms. It is the adenylic nucleotide ratio: E.C = (ATP + 1/2ADP)/ATP + ADP + AMP). We have measured this parameter to determine the state of health of these oysters. A methodological study has been conducted previously to define the conditions of sampling, conservation and extraction for a HPLC assay. The HPLC method (high performance liquid chromatography) is an adaptation of the HOFFMAN and LIAO (1977) method, that is performed with a C18 column and an isocratic elution with a pairing agent (tetrabutylammonium). A seasonal effect of nucleotide concentrations is observed (ANOVA test). Size exhibits no effect on the values of nucleotide concentrations. The highest values of nucleotides are observed in summer during the reproductive period. At this time, the variability of values is the highest too. In winter, the adenylic energy charge (AEC) is high and the concentrations of nucleotides low, suggesting a good physiological status of the oysters. We assume that the nucleotide variations express modifications in the metabolism level during a seasonal cycle. These results would be related to the capacity of the species to adapt its physiology depending on the seasonal constraints encountered in the field. Nous avons mesuré la charge énergétique de deux populations d'huîtres Crassostrea gigas, dans le cadre d'un suivi saisonnier à Marennes-Oléron, pour apprécier l'état de condition ou de santé de ces huîtres. On présume, en effet, que la baisse actuelle de production de ce bassin aurait pour origine une surcharge de biomasse qui se traduirait au niveau des huîtres par un affaiblissement général de ...